Common matrix metalloproteinase-2 gene variants and altered susceptibility to breast cancer and associated features in Tunisian women - Azza F Habel; Rabeb M Ghali; Hanen Bouaziz; Amira Daldoul; Mariem Hadj-Ahmed; Amina Mokrani; Sonia Zaied; Monia Hechiche; Khaled Rahal; Besma Yacoubi-Loueslati; Wassim Y Almawi (Tumor Biology, 2019)
A role for matrix metalloproteinase polymorphisms in breast cancer development and progression was proposed, but with inconclusive results. We assessed the relation of matrix metalloproteinase-2 variants with breast cancer and related phenotypes in Tunisians. This case-control retrospective study involved 430 women with breast cancer and 498 healthy controls. Genotyping of matrix metalloproteinase-2 rs243866, rs243865, rs243864, and rs2285053 was analyzed by allelic exclusion. The minor allele frequency of rs2285053 was significantly lower in women with breast cancer cases as compared to control women; minor allele frequencies of the remaining single-nucleotide polymorphisms were similar between cases and control women. The distribution of rs243865 and rs2285053 genotypes was significantly different between breast cancer patients and control subjects. This persisted when key covariates were controlled for. None of the matrix metalloproteinase-2 variants were associated with estrogen receptor positivity, progesterone receptor positivity, or with double estrogen receptor–progesterone receptor positivity in breast cancer patients. Matrix metalloproteinase-2 rs243866, rs243865, and rs243864 were positively associated with menstrual irregularity and histological type, while rs243866 and rs2285053 were negatively associated with menarche and nodal status. In addition, rs2285053 was negatively associated with triple negativity, tumor size, distance metastasis, molecular type, and chemotherapy. Haploview analysis revealed high linkage disequilibrium between matrix metalloproteinase-2 variants. Four-locus Haploview analysis identified haplotypes G C TT and GTT C to be negatively associated with breast cancer, which remained statistically after controlling for key covariates. Matrix metalloproteinase-2 alleles and genotypes, along with four-locus haplotypes, are related to reduced susceptibility to breast cancer in Tunisian women, suggesting a protective effect.